INFLUENCE OF MOTIVATION AND LANGUAGE LEARNING ENVIRONMENT ON THE SUCCESSFUL EFL LEARNING - Masyhur Masyhur (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
The research seeks to investigate successful learners’ motivational changes and learning histories from the first time they studied English until the achievement of high proficiency in the foreign language in Riau Province Indonesia. The central research questions are to reveal what motivational changes and learning histories successful learners display and how these learners have sustained their learning motivation until they eventually achieved high level of proficiency while studying in EFL environments. The participants are six adults who have achieved high levels of English proficiency. The design used in this case study involves both holistic and specifically focused analyses, by which each participant’s learning history is collected through individual interviews. The research reports each participant’s learning history, and the initial proposition concerning motivational change and salient motivational sources found in the participants’ learning histories are collectively analyzed and discussed. Exploring the data concerning how the participants have sustained their language learning motivation resulting in the idea that sustained motivation is not always present in successful foreign language learning. What make these six successful EFL learners different from other learners in Riau are their perseverance and intensively-prioritized EFL learning. In other words, they develop a more intentional psychological force, known as commitment. The results provide new, engaging, and important information to people who are seriously involved in foreign language learning in EFL contexts, especially Riau Province where the majority of learners fail to attain high levels of foreign language proficiency after receiving years of formal education.